The Agrico Soda Ash Story: Environmental and Metallurgical Advantages of Soda Ash as an Ammonia Replacement in the Float Plant - Charles T. Staniek (Society for Mining, Metallurgy & Exploration, 1993)
Following a dragline relocation at Agrico's Fort Green phosphate mine in 1986, the recovery plant experienced a significant decrease in flotation performance. Through weeks of trial and error testing, we discovered we could restore recoveries by conditioning feed at pH's higher than we had used historically. The higher pH's essentially increased flotation cell kinetics, although we still do not understand the exact mechanism at work. Armed with new-found appreciation of pH modification, we initiated a program to determine the optimum modifier for us, from both a performance and environmental perspective. Environmental considerations were important because ammonia, the standard industry modifier, is a plant nutrient and higher usage rates could affect the quality, of our recycle process water. This paper describes the research and development work spanning a 3 year period that culminated in making a major change in our reagent suite when we replaced ammonia with soda ash on a permanent full-time basis.